2012
DOI: 10.31638/ijprs.v1.i1.00017
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of HPTLC Method for Simultaneous Analysis of Lopinavir and Ritonavir in their Combined Tablet Dosage Form

Abstract: Simultaneous quantification of Lopinavir and Ritonavir in tablet by HPTLC method was developed and validated. The chromatograms were developed using a mobile phase of Chloroform: 1, 4 -Dioxane (7:3 %v/v) on pre-coated plate of silica gel GF aluminum TLC plate and quantified by densitometric absorbance mode at 210 nm. The R f value for lopinavir and ritonavir was 0.74 and 0.58 respectively. The linearity of the method was found to be within the concentration range of 160-960 ng/spot for Lopinavir and for Ritona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A literature survey revealed that there are several methods for the determination of DAR (Babu et al, 2013;Eswarudu et al, 2018) alone and DAR combined with other drugs also reported (Nalini et al, 2016;Fayet et al, 2009). The different analytical methods for the estimation of RIT (Behera et al, 2011;Koppala et al, 2015) alone and combined with other drugs have been reported (Mardia et al, 2012;Saritha et al, 2013). There are very few analytical methods for the simultaneous determination of DAR and RIT estimation are reported (Damle and Deosthali, 2016;Prathap et al, 2018).…”
Section: Figure 2: Chemical Moiety Of Darunavirmentioning
confidence: 99%
“…A literature survey revealed that there are several methods for the determination of DAR (Babu et al, 2013;Eswarudu et al, 2018) alone and DAR combined with other drugs also reported (Nalini et al, 2016;Fayet et al, 2009). The different analytical methods for the estimation of RIT (Behera et al, 2011;Koppala et al, 2015) alone and combined with other drugs have been reported (Mardia et al, 2012;Saritha et al, 2013). There are very few analytical methods for the simultaneous determination of DAR and RIT estimation are reported (Damle and Deosthali, 2016;Prathap et al, 2018).…”
Section: Figure 2: Chemical Moiety Of Darunavirmentioning
confidence: 99%